Unpacking augmentation quality and local presence: Factors that drive effective augmented reality marketing - Katrin E. Schein; Philipp A. Rauschnabel; Sandra Praxmarer-Carus; Barry J. Babin (Journal of the Academy of Marketing Science, 2025)
Augmented reality (AR) integrates virtual content into consumers' physical environment. Although research suggests that consumers' perceptions of augmentation quality—the perceived merge of the~virtual and real world—affect relevant consumer variables, the literature has not developed a comprehensive measure that adequately captures the construct nor integrated it meaningfully with theory-relevant outcomes. Grounded theory and standard scale development procedures are applied to understand what comprises perceptions of augmentation quality and how to measure it to distinguish low- from high-quality AR-marketing attempts. The findings suggest that quality perceptions in AR consist of a second-order factor, augmentation quality, represented by three first-order factors (design, interaction, and embedding quality). In addition, this research demonstrates that high augmentation quality creates a sense of local presence, i.e., the sensation that the augmented object experienced with AR is real and present to the consumer. The research then theoretically integrates these factors into a more comprehensive model, tying it firmly into the nomological net. In particular, augmentation quality—mediated by local presence—affects utilitarian and hedonic outcomes as well as behavioral actions. Managerial implications for understanding and using AR marketing are presented.
Keywords: 330; Augmented reality; Augmentation quality; Local presence; Scale development; Shopping experience